THE STRATEGY OF NATIONAL VALUES DEVELOPMENT BASED ON RELIGIOUSITY FRONT PEMBELA ISLAM (FPI) IN PURWAKARTA REGENCY - Cecep Darmawan, Ating Supardi, Sapriya, (Jurnal Civicus, 2015)
This study used a qualitative approach with a phenomenological method for assessing the relationship between subjective and objective reality of meaning in everyday life. The results showed that patriotism was seen as a manifestation love of Allah, therefore FPI have a core program it relevant to build national values, include; hisbah, halaqoh, and syahriahan. Recommendations offered include; increase the participation of nation building through involvement in various social activities, enhance cooperation, communication and coordination with various stakeholders of mental and moral development efforts of generations, and necessity to build communities of people that support the implementation of development in all areas.